Facile synthesis of a novel transparent melt‐spinnable polysilazane. Issue 4 (21st August 2021) - Chen, Jianjun; Li, Hailong; Kao, Kechen; Lin, Wenxin; Xiong, Yilian; Huang, Zhengren
Abstract: In this study, a novel colorless and transparent polysilazane (PSZ) with excellent spinnability was facilely synthesized via the thermal polymerization of silazane oligomer at 330℃. The silazane precursor was fabricated by one‐step copolycondensation of methyldichlorosilane (CH3 SiHCl2 ) and dimethyldichlorosilane ((CH3 )2 SiCl2 ) in various ratios at 0℃ without catalyst during the reaction. The chemical composition, molecule structure, molecular weight and ceramic yield of PSZ were investigated by gel permeation chromatography (GPC), Fourier transform infrared (FT‐IR), thermogravimetric analysis (TGA) and pyrolysis chromatography‐mass spectrometry (PY‐GC/MS). The optimized novel transparent melt‐spinnable PSZ was a colorless and transparent brittle solid with a Mw = 14, 231 and a melting point of 100℃, which was prepared with an optimal molar ratio of raw materials at 1.9:1 (CH3 SiHCl2 : (CH3 )2 SiCl2 ). Fibers with various diameters were spun using a homemade melt spinning setup at 90–120°C. The obtained PSZ showed outstanding spinnability, and the prepared continuous fibers exhibited a uniform diameter (10–80 microns) and a smooth surface up to 1000 meters long. In addition, possible polymerization mechanisms of PSZ were also discussed. The PSZ showed the excellent rheological properties in melt‐spinning as a potential precursor for Si3 N4 fibers. The novel optically transparent polysilazane material also have great potential applications in optical technology and engineering. Abstract : In this paper, a series of colorless and transparent polysilazanes were synthesized through the ammonolysis reaction without catalyst. The obtained polysilazane has excellent continuous spinning performance, and the spun fiber has a uniform diameter and a smooth surface. The fiber length can reach 1000 m and the diameter ranges from 10 to 80 µm.